Component based modelling for animated educational queuing networks - Khalid, Ruzelan; Kreutzer, Wolfgang; Bell, Tim (IACSIT Press, 2011)
This paper presents two well known design patterns that are appropriate for designing Interactive Simulation components for educational purposes. These are the Delegation Event Model, used for linking between components, and the MVC (Model-View-Controller) pattern, used for connecting the components to their visualizations and graphical user interfaces (GUIs).Combining both architectures, we have constructed Discrete Event Simulation (DES) components for modelling queuing networks in the Flash environment.The resulting components not only help teachers with little programming skill to construct simulation models, but also allow learners to conduct various experiments through interactive Graphical User Interfaces (GUIs) and obtain feedbacks of model behaviour through a range of engaging visualizations.